(untitled) (Feni University Journal, 2026)
This paper attempts to investigate whether there exists any relationship between the personality dimensions of faculties working in private and public universities and their teaching performances. McCrae and Costa [1] state that personality characteristics are evaluated through five extensive general dimensions: extraversion, agreeableness, conscientiousness, neuroticism, and openness to new experiences, as illustrated in the Big Five Model. This study used a questionnaire comprised of 30 items on a sample of 72 faculty respondents who belong to the universities located in Dhaka and Chittagong - the two historically famous districts of Bangladesh. For analyzing data, appropriate statistical tools are used and interpreted meaningfully. The present study finds significant positive but different levels of association between personality dimensions and teaching performance. The paper is expected to add a new horizon to the literature on quality teaching in universities. Recommendations for further research initiatives are also forwarded at the end portion of the paper. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (103-112)